Review of crayfish color patterns in the Family Cambaridae (Astacoidea), with discussion of their possible importance - Schuster, Guenter A. (Zootaxa, 2020)
The use of color photographs in crayfish species descriptions, state faunal books and popular articles is relatively recent. Except for verbal color descriptions, color and color patterns have not often been explored by crayfish researchers. Carotenoids and carotenoproteins are responsible for much of the color found in the integument and exoskeleton of crayfishes and other crustaceans. Research has shown variation in color may be the result of the environment, diet, molt stage and age, genetics, or a combination of these. Crayfishes possess color vision, may use polarization vision, and have the possibility of fluorescent vision. They also have very good low light vision. Crayfishes have a multichromatic range in color sensitivity; it ranges from blue to red, with no UV sensitivity. Color vision may be an important factor in intraspecific and interspecific competition, territoriality, camouflage, sexual selection, and communication. A distinction is made between base or background colors displayed in crayfishes and their exhibited color patterns. While actual base or background colors may vary among individual crayfishes, a case is made that color patterns show much less intraspecific variation. Distinct color patterns are the result of highly contrasting colors on appendages or parts of appendages such as chelae, leg joints, tail fan, spines, and tubercles. Body regions like the carapace and abdomen may also have contrasting spots, bands or stripes. Color patterns may be useful in better understanding crayfish taxonomy, phylogeny, and evolutionary convergence, and examples are provided.